Sasana Kapamangkuan: Sebuah Ajaran Tattwa dan Etika dalam Membangun Kesadaran Diri Sebagai Pelayan Umat - I Made Pasek Subawa; Putu Sri Junianti (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The tradition of using my uncle or priest arises because the Hindu community since ancient times has been divided into professional groups. The Brahmin group has a profession in the religious field, because it is seen as the group that best understands religious teachings including its ceremonial procedures, because it is natural when a priest is declared as an intermediary between the Ummah with Ida Sang Hyang Widhi Wasa and Ida Bhatara Kawitan. The presence of my uncle is a necessity for Hindus wherever he is. Its capacity and function become very important or vital as does the presence of a pandita. Its existence and role is very much needed when Hindus carry out religious life in the social dimension or diversity in the communal aspect. Therefore, for my uncle it is very important to know and understand the lontar-palm associated with my uncle's atmosphere, one of which is Kusumadewa ejection. As one of the palms containing tattwa, ethics, and ceremonies, the palms of Kusumadewa can be one of the fundamental references for my uncle who is just beginning to know the teachings of kapamangkuan.